Detecção e genotipagem do papilomavírus humano (HPV) em mulheres HIV-positivas e em controles de Goiânia-GO - Vaz, Luciana Pinheiro (2009)
Genital infection with the human pappilomavirus (HPV) is considered to be the most frequent sexually transmitted disease in the world, representing an important public health problem due to its close association with cervical cancer. It is estimated that 75% of the sexually active population comes into contact with one or more types of HPV during their livetime, resulting in a considerably high prevalence of the virus in young women. Epidemiological studies shows that women infected by the human immunodeficiency virus (HIV) presents a higher prevalence of infection by HPV and a greater association with multiple genotypes of HPV compared those who are HIV negative. The objective of this study was to compare the prevalence of HPV infections and its possible risk factors in a group of HIV positive and HIV negative women, in the city of Goiania GO. Polimerase chain reaction, using generic primers GP5+/GP6+, was carried out to detect the viral genome and specific primers were used for HPV-16 and HPV-18 genotyping. The study included a population of 60 HIV soropositive women, assisted by CADA (Centro de Apoio ao Doente com AIDS), and 60 HIV soronegative women selected in June, 2007, during a Public Health Program conduced by the Universidade Católica de Goiás. All the patients were informed about the study and signed an informed consent. Both groups were similar concerning social demographics and behavioral characteristics, however, significant differences were observed among their marital status, household income, educational status, number of sexual partners, prostitution history and tobacco smoking. The prevalence of HPV infection was 64.3% among women who were HIV positive and 32.5% among those who were HIV negative. HPV-16 was the most prevalent type in both groups, with a prevalence of 67.5% in HIV positive women and 32.5% in HIV negative women. Among the women who presented CIN I, all were HIV positive and in those who presented CIN II/CIN III, 85.7% were HIV positive. The combination between HPV-16 and HPV-18 genotypes was present in 72.2% of the HIV positive women, and in 27.8% of the HIV negative women. Our study demonstrated a greater HPV infection prevalence in those women infected with HIV compared to those who were HIV negative. HPV-16 was the most commonly found genotype in both groups, however, dual infections with HPV-16 and HIP-18 were significantly more prevalent in those women infected with HIV. Our results allowed us to conclude that infection with HIV represents a significant risk factor for the HPV infection.